Analysis of Effectiveness Instagram as a Promotional Media for Akkar Juice Bar Products - Rizky Ananda Putri; Novita Erma Kristanti; Atris Suyantohadi (Agroindustrial Journal, 2023)
The number of internet users in Indonesia has been rising annually. A growing number of people are using social media including Instagram as a communication tool for digital marketing. Since the beginning of the company, Akkar Juice Bar has utilized Instagram to reach out to and interact with customers as well as to introduce its products. Using the CRI (Customer Response Index) with AISAS (Attention, Interest, Search, Action, Share) method, this study aims to measure Instagram's effectiveness as a promotional tool for Akkar Juice Bar. Based on the findings of this analysis, promotion recommendations are made. Instagram's effectiveness as a marketing medium is evaluated by a CRI calculation with a modified AISAS model. These calculations include CRI AIS of 77.17%, CRI AISS of 72.72%, CRI AIAS of 60.85%, and CRI AISAS of 57.34%. The four obtained CRI model values provide valuable information in general. To make the greatest impact of promotions, it is advised to use Instagram Ads for advertising, run consumer-driven campaigns and competitions, reward consumers who share, feature customer testimonial posts, and make posts more intense.